The principle of in dubio pro tributario in tax relations - UGOLKOV, Євген (Ius Modernum, 2025)
The norms of the Tax Code of Ukraine provide for the application of the principle of presumption of legality of taxpayer decisions (in dubio pro tributario) in the case of the existence of a "poor-quality law" as a result of which the regulatory authority cannot make a decision, that leads to a deterioration in the situation of such a taxpayer. The presence of such a principle in tax legislation leads to the taxpayer's expectation that in the case of an ambiguous (multiple) interpretation of taxpayers' rights and obligations, any decisions will be made on the condition that the situation of such taxpayer does not "deteriorate". The scientific approaches and individual aspects of the practical application of the presumption of legality of taxpayer decisions in tax legal relations have been studied. Scientific ideas regarding approaches to content disclosure are analyzed. The study showed that in practice, regulatory authorities neglect the application of the specified principle, as a result of which there is no legal consolidation of a clear and effective mechanism for the practical application of the presumption of legality of taxpayer decisions in tax legal relations. Based on the problems identified in the study, clear practical recommendations have been proposed to improve the legal regulation of the practical application of the presumption of legality of taxpayer decisions in tax legal relations, in particular during the conduct of control and verification activities. The results of the study can be used to improve Ukrainian legislation in the field of tax relations, in particular regarding the protection of taxpayersʼ rights.